Some results on open-edge and open mobile guarding of polygons and triangulations - Bajuelos, Antonio Leslie (2015)
This paper focuses on a variation of the Art Gallery problem that considers open-edge guards and open mobile-guards. A mobile guard can be placed on edges and diagonals of a polygon, and the ‘open’ prefix means that the endpoints of such an edge or diagonal are not taken into account for visibility purposes. This paper studies the number of guards that are sufficient and sometimes necessary to guard some classes of simple polygons for both open-edge and open mobile-guards. A wide range of polygons is studied, which include orthogonal polygons with or without holes, spirals, orthogonal spirals and monotone polygons. Moreover, this problem is also considered for planar triangulation graphs using open-edge guards.